2021
DOI: 10.1111/pin.13067
|View full text |Cite
|
Sign up to set email alerts
|

B cell lymphoma with IRF4 rearrangement: A clinicopathological study of 13 cases

Abstract: Interferon regulatory factor 4 (IRF4) rearrangement is commonly detected in patients with a range of lymphoproliferative malignancies, including myelomas, large B cell lymphomas and low‐grade B cell neoplasms. However, IRF4 rearrangement is generally a relatively rare finding in these latter two cancer types. In the present article, we describe and summarize the clinicopathological and genetic features of 13 cases of B cell lymphoma with IRF4 rearrangement, including 12 cases of large B cell lymphoma and one c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…By now, a single case of an extremely rare low-grade B-cell lymphoma with IRF4 rearrangement with concomitant mutation in SAMHD1 (c.G692A; leading to premature a stop codon, W231X) was described [ 25 ]. Probably, this early stop-gain mutation in SAMHD1 will lead to reduced protein expression, which was not assessed in the report by Zhou et al In this patient, further missense and frameshift mutations were detected in the genes KMT2D , BTG1 , PTEN , and BAX [ 25 ].…”
Section: Samhd1 Mutations Reported In Various Cancer Typesmentioning
confidence: 99%
“…By now, a single case of an extremely rare low-grade B-cell lymphoma with IRF4 rearrangement with concomitant mutation in SAMHD1 (c.G692A; leading to premature a stop codon, W231X) was described [ 25 ]. Probably, this early stop-gain mutation in SAMHD1 will lead to reduced protein expression, which was not assessed in the report by Zhou et al In this patient, further missense and frameshift mutations were detected in the genes KMT2D , BTG1 , PTEN , and BAX [ 25 ].…”
Section: Samhd1 Mutations Reported In Various Cancer Typesmentioning
confidence: 99%
“…The presence of macrophages with tingible bodies as well as dispersed apoptotic debris in the background, albeit reported in some papers is classically not described in this entity. 1,9,10 No immunoblastic-like cells, Sternberg Reed cells, pleomorphic cells or cells expressing CD30 were identified in our case. We also did not identify the presence of dendritic cells or histiocytes.…”
Section: Discussionmentioning
confidence: 52%
“…Large B-cell lymphoma with IRF4 rearrangement lacks the starry sky appearance seen in PTFL. Moreover, an immunohistochemistry study showed BCL2 positivity in more than half of the cases with strong IRF4 / MUM1 expression [ 14 , 23 , 24 , 31 ].…”
Section: Differential Diagnosismentioning
confidence: 99%